ANALISIS METODE PENCATATAN DAN PENILAIAN PERSEDIAAN PADA PT. DHARMA RAYA ANUGERAH CANDRA DI SAMARINDA (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
PT. Dharma Raya Anugerah Candra is a company engaged in the procurement of goods and services in this case the procurement of Air Conditioner (AC), Spare Parts, Service Air Conditioner and other electronic equipment. The formulation of the problem in this research is inventory valuation method of recording and Air Conditioning (AC) at PT. Dharma Raya Anugerah Candra are in accordance with Financial Accounting Standards Entities Without Public Accountability (SAK-ETAP) Chapter 11 on supplies. The purpose of this study was to determine the suitability of the inventory valuation method of recording and Air Conditioning (AC) applied by PT. Dharma Raya Anugerah Candra with (SAK-ETAP) In Chapter 11 on the supplies. The analysis tool used is using a FIFO inventory valuation method perpetual referring to the SAK-ETAP about inventories and comparing the value of ending inventory according to company calculations and analysis according to the calculations of SAK-ETAP. After doing research ,the final inventory valuation PT. Dharma Raya Anugerah Candra does not correspond to the final inventory valuation based SAK-ETAP about inventory using First In First Out .This is due to errors in recording inventory cards irregular and consistent with the method used up causing balance that does not correspond to the real situation.Keyword: Recording and Assessment Inventory, SAK-ETAP.